Elementary transition systems - Nielsen, Mogens; Rozenberg, Grzegorz; Thiagarajan, P. S. (DAIMI Report Series, 1990)
Transition systems are a simple and powerful formalism for explaining the operational behaviour of models of concurrency. They provide a common framework for investigating the interrelationships between different approaches to the study of distributed systems. Hence an important question to be answered is: which subclass of transition systems corresponds to a particular model of distributed systems? In this paper we provide an answer to this question for elementary net systems.